Genotypic pattern of fluoroquinolone resistance among extended-spectrum beta-lactamase-producing Escherichia coli - Febrianti, Tati; Puspandasari, Nelly; Febriyana, Dwi; Weaver, Tom; Karuniawati, Anis (Medical Journal of Indonesia, 2024)
BACKGROUND Fluoroquinolone (FQ) is one of the therapeutic options for treating extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli (ESBL-Ec) infection, but its use could increase the resistance level of ESBL-Ec. This study aimed to analyze the resistant genes responsible for ESBL production and FQ resistance among the ESBL-Ec isolated from healthy humans and communal wastewater. METHODS This was an observational study using stored isolates and laboratory data. Genome sequencing was done on 43 E. coli DNA isolates before resistance genes, mutations, and high-risk clones were examined through bioinformatic data analysis. RESULTS The analysis of 39 ESBL-Ec isolates showed ESBL genes, including blaCTX-M-55 (56%), blaCTX-M-15 (31%), and blaCTX-M-27 (8%). ESBL-Ec isolates exhibited mutations in gyrA (54%), gyrB (0%), parC (28%), and parE (10%). Plasmid-mediated quinolone resistance genes detected included qnrS1 (54%), qnrS13 (13%), qnrB2 (3%), aac(6’)-Ib-cr5 (3%), qepA (0%), and oqxAB (0%). ESBL and FQ resistance genes were simultaneously detected in 33 ESBL-Ec isolates, with high-risk clones identified as ST155, ST10, ST23, ST38, ST131, and ST69 Cplx. CONCLUSIONS ESBL and FQ resistance genes were simultaneously detected in ESBL-Ec isolated from healthy humans and communal wastewater.